2012
DOI: 10.1371/journal.pone.0037652
|View full text |Cite
|
Sign up to set email alerts
|

Meandering Main Pancreatic Duct as a Relevant Factor to the Onset of Idiopathic Recurrent Acute Pancreatitis

Abstract: BackgroundMeandering main pancreatic duct (MMPD), which comprises loop type and reverse-Z type main pancreatic duct (MPD), has long been discussed its relation to pancreatitis. However, no previous study has investigated its clinical significance. We aimed to determine the non-biased prevalence and the effect of MMPD on idiopathic pancreatitis using non-invasive magnetic resonance (MR) technique.Methods and FindingsA cross-sectional study performed in a tertiary referral center. The study enrolled 504 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Gonoi et al . 16 evaluated that 2.2% (11/504) of subjects had loop and reverse-Z type pancreatic course in Japanese. In our study group, descending course was found in about 62.5%, sigmoid course 30% and vertical course 5.5%, loop course 2%, so the prevalence of vertical and sigmoid course were marked different from their value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gonoi et al . 16 evaluated that 2.2% (11/504) of subjects had loop and reverse-Z type pancreatic course in Japanese. In our study group, descending course was found in about 62.5%, sigmoid course 30% and vertical course 5.5%, loop course 2%, so the prevalence of vertical and sigmoid course were marked different from their value.…”
Section: Discussionmentioning
confidence: 99%
“…Gonoi et al . 16 evaluated that the prevalence of pancreas divisum was 2.6 (13/504) in Japanese. We found a prevalence rate of pancreas divisum 4.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects having the following findings were excluded: (1) spindle, cudgel, stick, or branch types of the terminal portion of the dorsal pancreatic duct, in which the calibre changes smoothly (Figure 1) [8-10]; (2) neoplasm in the dorsal portion of the head of pancreas; (3) suspected intraductal papillary mucinous neoplasm in the dorsal pancreatic duct; and (4) other major malformation such as abnormal arrangement of pancreaticobiliary ducts or choledochocele. Minor ventral ductal anatomical variation that does not seem to change the flow of pancreatic juice in the dorsal pancreatic duct, such as meandering main pancreatic duct (loop type or reverse-Z type) [17] may exist. Santorinicele with pancreas divisum (SWPD) was diagnosed for a santorinicele accompanied by pancreas divisum (classical type, pancreas divisum with absent ventral duct, incomplete type) [16] using the same exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, serious damage of pancreatic tissue leads to dysfunction of the endocrine and exocrine systems, particularly in the chronic phases of the disease. There are several known causes of pancreatitis, including excessive alcohol consumption, biliary stones, trauma, autoimmunity, metabolic disorders, drugs, iatrogenic, infection, genetic mutations, malignancy, and heredity factors[1-3]; and morphological aberrations such as atypical arrangement of the pancreaticobiliary ductal system[4,5], pancreas divisum[5-8], or a meandering main pancreatic duct[9]. However, recurrent episodes of acute pancreatitis is idiopathic in as many as 20% of patients[8,10,11].…”
Section: Introductionmentioning
confidence: 99%